Analisis Profil Penggunaan Layanan Peer-to-peer Lending Pada UKM di Kota Salatiga - Kristianti, Ika (Jurnal Ilmiah Manajemen Kesatuan, 2020)
The COVID-19 pandemic in Indonesia has inflicted an inevitable income drop to many businesses, including Small Medium Enterprise (SME). In order to continue running their operational activities and keep fulfilling its obligations, some SMEs started to use P2P lending services as one of its capital sources. The purpose of this study is to portray the profile of P2P lending user, especially in Salatiga. This research is conducted by using qualitative research methodology with descriptive approach. Some SMEs believe that P2P lending can provide them with support in fulfilling their obligations. But in the other hand, there are others which argue that the services provided by P2P lending are inefficient and ineffective in fulfilling their business obligations.